An investigation into the molecular basis of cancer comorbidities in coronavirus infection. Issue 11 (12th October 2020) - Facchiano, Antonio; Facchiano, Francesco; Facchiano, Angelo
Abstract : Comorbidities in COVID‐19 patients often worsen clinical conditions and may represent death predictors. Here, the expression of five genes, known to encode coronavirus receptors/interactors ( ACE2, TMPRSS2, CLEC4M, DPP4 and TMPRSS11D ), was investigated in normal and cancer tissues, and their molecular relationships with clinical comorbidities were investigated. Using expression data from GENT2 databases, we evaluated gene expression in all anatomical districts from 32 normal tissues in 3902 individuals. Functional relationships with body districts were analyzed by chilibot . We performed DisGeNet, genemania and DAVID analyses to identify human diseases associated with these genes. Transcriptomic expression levels were then analyzed in 31 cancer types and healthy controls from approximately 43 000 individuals, using GEPIA2 and GENT2 databases. By performing receiver operating characteristic analysis, the area under the curve (AUC) was used to discriminate healthy from cancer patients. Coronavirus receptors were found to be expressed in several body districts. Moreover, the five genes were found to associate with acute respiratory syndrome, diabetes, cardiovascular diseases and cancer (i.e. the most frequent COVID‐19 comorbidities). Their expression levels were found to be significantly altered in cancer types, including colon, kidney, liver, testis, thyroid and skin cancers ( P < 0.0001); AUC > 0.80 suggests that TMPRSS2, CLEC4M and DPP4 are relevant markers of kidney, liver, and thyroid cancer, respectively. The five coronavirus receptors are related to all main COVID‐19 comorbidities and three show significantly different expression in cancer versus control tissues. Further investigation into their role may help in monitoring other comorbidities, as well as for follow‐up of patients who have recovered from SARS‐CoV‐2 infection. Abstract : Five receptors/interactors of coronaviruses may play a key role in COVID‐19 comorbidities. They are expressed in almost any body district and, regardless of coronavirus infection, are associated with several diseases, including those most frequently cooccurring in COVID‐19 patients. Their expression is strongly altered in many cancers and at least three of them may be relevant markers in kidney, liver and thyroid cancers.